Political Diversity Culture of Kiai at Annuqayah Pesantren, Guluk-Guluk, Sumenep - Mahsun, Robith; Asiz, Abdul (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2024)
Political diversity among kiai within pesantren institutions remains an underexplored phenomenon in Islamic educational leadership, particularly regarding how such diversity is managed without compromising institutional unity. This study examines the culture of political diversity among kiai at Annuqayah Pesantren, Guluk-Guluk, Sumenep, with three objectives: identifying factors shaping kiai's diverse political orientations, analyzing strategies sustaining institutional cohesion amid political differences, and exploring the relationship between political diversity culture and educational values transmitted to students. A qualitative approach was employed through in-depth interviews, participant observation, and documentation. Subjects were selected purposively from kiai actively engaged in diverse political activities. Data analysis followed systematic stages of collection, classification, reduction, and conclusion drawing, grounded in Almond and Verba's political culture theory. Three findings emerge. First, political diversity at Annuqayah stems from differences in ideological interpretation, variations in information, and social conformity patterns. Second, kiai manage political differences through cultivating silaturrahim, safeguarding institutional reputation, exercising contextual wisdom, and providing mutual support for kiai in practical politics. Third, political diversity culture is constructively linked to the pesantren's educational mission of cultivating civil society (masyarakat madani) grounded in Ahlus Sunnah wal Jama'ah principles. These findings suggest that political diversity, when managed through institutionally embedded cultural norms, functions as a constructive force for democratic education within the pesantren.